PCA effect on structure of fly ashes and slag obtained by mechanosynthesis. Applications: Mechanical performance of substituted paste CEMI + 50% slag /or fly ashes. (10th April 2019) - Bouchenafa, Othmane; Hamzaoui, Rabah; Bennabi, Abdelkrim; Colin, Johan
Highlights: Nanostructured materials obtained by Mechanosynthesis. Milled co-product increase mechanical performances of substituted cement. High-energy milling tends to produce more agglomerated particles. The use of PCA reduce agglomeration phenomena. Co-products mechanical activation improve pozzolanic reactions. Abstract: In this study, we have modified slag and fly ashes by mechanosynthesis process carried out by high-energy ball milling using a planetary mill. In order to optimize the milling conditions, we have added process control agent (PCA). This PCA affects powders agglomeration phenomena during milling and impacts the milling time for the final product. We have studied the structure and microstructure of coproducts (fly ashes and slag) obtained by mechanical activation. In addition, we have also tested the mechanical performances of samples prepared with the addition of activated coproducts.